The assessment of a sense of initiative and entrepreneurship in VET - Morselli, Daniele (Formazione & insegnamento, 2018)
This article presents a framework for the assessment of learning outcomes concerning a sense of initiative and entrepreneurship as cross-curricular subject. It seeks to solve two issues: competence and its assessment, and assessment of learning occurred as cross-curricular subject. This paper claims that the key competence of a sense of initiative and entrepreneurship and the European Qualification Framework are useful tools to assess entrepreneurial learning outcomes. The assessment is performed through problem solving situations which are new for the learner and related to his or her qualification. A case study shows an assessment program of knowledge, skills and attitudes related to a sense of initiative and entrepreneurship carried out in two vocational schools. Results suggest the need for a better alignment between work-alternation, teaching for competence, and assessment of key competences.